Contribution of nitrogen and phosphorus from combined application of Azotobacter and phosphobacteria in potato - Jatav, MK; Dua, VK; Kumar, Manoj; Khurana, SC; Bhatia, AK; Nandekar, DN; Manorama, K; Trivedi, SK; Das, SN; Chettri, M; Raghav, Manoj; Verma, RB; et al. (Vegetable Science, 2012)
Field experiments were conducted at AICRP centers viz Bhubaneswar, Chhindwara, Hisar, Kalyani, Kota, Modipuram, Ooty, and Pantnagar to investigate the role of biofertilizers (Azotobacter + Phosphobacteria) and Bacillus inoculation for nitrogen and phosphorus economy in potato crop. The treatment tuber soaking with 1% urea and sodium bicarbonate along with combined application of Azotobacter and PSB at both the fertility levels gave the highest yield at Ooty, Hisar, Chhindwara, Bhubaneswar, Faizabad, Kalyani and Pantnagar and was significantly better than the treatment receiving 100% recommended dose of fertilizers of nitrogen and phosphorus and 75% recommended dose of fertilizers of nitrogen and phosphorus application (100% of RDF of NP &75% of RDF of NP). At Faizabad, Hisar and Chhindwara, Bacillus tuber treatment was at par with tuber soaking with 1% urea and sodium bicarbonate along with biofertilizers application (Azotobacter and PSB) indicating possibility of saving 25% recommended dose of fertilizers of nitrogen and phosphorus at these places using seed soaking and bio-inoculants or Bacillus treatment. The yield trend was reflected in net returns also at the entire centre. At Kota centre the use of B subtilis gave the highest yield and net return which was followed by Bacillus cereus and tuber soaking and biofertilizer